Comparative Analysis of Public Healthcare Service Delivery Systems in France and Korea - 이유현; 이채정 (한국비교정부학보, 2021)
(Purpose) This study aims to present the direction of future public healthcare service delivery systems through in-depth comparative analysis in France and Korea. Through this paper, we aims to understand how government and market relationships are established to provide social services in the two countries. We also expect to be able to identify its differential characteristics. (Design/methodology/approach) A two-step qualitative approach is conducted. First, the research examines the commonalities and differences of the public healthcare service delivery system in France and Korea, which are considered as social insurance-based welfare states. Second, the study evaluates the role of the state-to-market among countries with similar social welfare systems. For the comparison, Germany and Japan, social insurance-based welfare states, are chosen as the comparative groups. (Findings) The characteristics of the public healthcare service delivery system in France and Korea are analyzed. Additionally, the level of government intervention in the public healthcare service delivery systems is measured. According to the analysis, France has a low rate of self-charge, and the proportion of healthcare, public hospitals, and public beds among public funds was high. Therefore, France is more of a complete government intervention model. Subsequently, in Korea, the percentage of self-payment was high, and the percentage of healthcare, public hospitals, and public beds was low among public funds. Thus, Korea is close to a complete market intervention model and has the opposite public healthcare service delivery system compared to France. (Research implications or Originality) This study presents some rationales for expanding public hospitals and beds in align with the reinforcement of the publicness of health service. The two-stage qualitative analysis methodology identified the characteristics of the public healthcare service delivery systems of both countries.
Keywords: Public Healthcare; Social Service Delivery System; Welfare State; France; 공공의료; 사회서비스 전달체계; 복지국가; 프랑스